Unique Kinetic Properties of Phenol-Degrading Variovorax Strains Responsible for Efficient Trichloroethylene Degradation in a Chemostat Enrichment Culture - Futamata, Hiroyuki (American Society for Microbiology, 2005)
A chemostat enrichment of soil bacteria growing on phenol as the sole carbon source has been shown to exhibit quite high trichloroethylene (TCE)-degrading activities (H. Futamata, S. Harayama, and K. Watanabe, Appl. Environ. Microbiol. 67:4671-4677, 2001). To identify the bacterial populations responsible for the high TCE-degrading activity, a multidisciplinary survey of the chemostat enrichment was conducted by employing molecular-ecological and culture-dependent approaches. Three chemostat enrichment cultures were newly developed under different phenol-loading conditions (0.25, 0.75, and 1.25 g liter(−1) day(−1)) in this study, and the TCE-degrading activities of the enrichments were measured. Among them, the enrichment at 0.75 g liter(−1) day(−1) (enrichment 0.75) expressed the highest activity. Denaturing gradient gel electrophoresis of PCR-amplified 16S rRNA gene fragments detected a Variovorax ribotype as the strongest band in enrichment 0.75; however, it was not a major ribotype in the other samples. Bacteria were isolated from enrichment 0.75 by direct plating, and their 16S rRNA genes and genes encoding the largest subunit of phenol hydroxylase (LmPHs) were analyzed. Among the bacteria isolated, several strains were affiliated with the genus Variovorax and were shown to have high-affinity-type LmPHs. The LmPH of the Variovorax strains was also detected as the major genotype in enrichment 0.75. Kinetic analyses of phenol and TCE degradation revealed, however, that these strains exhibited quite low affinity for phenol compared to other phenol-degrading bacteria, while they showed quite high specific TCE-degrading activities and relatively high affinity for TCE. Owing to these unique kinetic traits, the Variovorax strains can obviate competitive inhibition of TCE degradation by the primary substrate of the catabolic enzyme (i.e., phenol), contributing to the high TCE-degrading activity of the chemostat enrichments. On the basis of physiological information, mechanisms accounting for the way the Variovorax population overgrew the chemostat enrichment are discussed.